Substitution in the Ugarit and the Sound of the Ḍād Letter A Comparative Study between Ugaritic and Classical Arabic The first part of the topic: Replacement in the classical Arabic dialects; (Damascus University Journal of arts and humanities sciences, 2021)
The Importance of this study and its objective is to emphasize the old introduction of classical Arabic and dialects within the Arabian Peninsula. Therefore, it is important, in order to achieve this, that we move from the method that is limited to comparison between the Ugaritic and the classical Arabic followed by the researchers to the comparison between the Ugaritic dialect and the dialects of the tribes within the Arabian Peninsula. This new method enabled us to identify new features within the system of Ugaritic sounds, and therefore the contents of this part of the subject is to study substitution in the classical Arabic dialects and differences between them. The discussion focused mainly on the different opinions about the sound of the letter Ḍād (ض) and the developments it has been subject to over a long time, since the period called mother tongue down until Sibawayh and his book, and the subsequent other developments.